2012
DOI: 10.4172/1948-5956.1000105
|View full text |Cite
|
Sign up to set email alerts
|

The Aurora Kinase A Polymorphisms are not Associated with Recurrence-free Survival in Prostate Cancer Patients

Abstract: Background: The purpose of this study was to investigate the association between haplotype-tagging single nucleotide polymorphisms (SNPs) within the Aurora Kinase A (AURKA) gene and prostate cancer outcomes in patients with clinically localized prostate cancer. Methods:Four intronic haplotype-tagging SNPs within the AURKA gene were individually selected and examined in regard to their influence on clinical outcomes in 212 patients who underwent radical prostatectomy as first-line treatment. Haplotype-tagging S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
(16 reference statements)
1
7
0
Order By: Relevance
“…For example, rs2273535 (Phe31Ile) has been associated with colorectal, breast, lung, and esophageal cancer risk [Kimura et al, 2005;Lo et al, 2005;Cox et al, 2006;Hienonen et al, 2006;Chen et al, 2007;Gu et al, 2007;Vidarsdottir et al, 2007]. Similarly, rs1047972 (Ile57Val) significantly increased the risk of esophageal cancer development, as well as the risk of gastric cancer and its progression [Kimura et al, 2005;Ju et al, 2006;Jaboin et al, 2012;Mesic et al, 2016]. In addition, it was demonstrated that rs1047972 could enhance AURKA relative kinase activity [Ju et al, 2006].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, rs2273535 (Phe31Ile) has been associated with colorectal, breast, lung, and esophageal cancer risk [Kimura et al, 2005;Lo et al, 2005;Cox et al, 2006;Hienonen et al, 2006;Chen et al, 2007;Gu et al, 2007;Vidarsdottir et al, 2007]. Similarly, rs1047972 (Ile57Val) significantly increased the risk of esophageal cancer development, as well as the risk of gastric cancer and its progression [Kimura et al, 2005;Ju et al, 2006;Jaboin et al, 2012;Mesic et al, 2016]. In addition, it was demonstrated that rs1047972 could enhance AURKA relative kinase activity [Ju et al, 2006].…”
Section: Discussionmentioning
confidence: 99%
“…Aurora kinase A ( AURKA ) is a serine/threonine kinase and well known oncogene, which plays an important role in centrosome maturation and separation, chromosome alignment, mitotic spindle assembly, mitotic entry and cytokinesis [Fu et al, ; Tchatchou et al, ; Jaboin et al, ; Gavriilidis et al, ]. Aurora kinase B ( AURKB ) is part of the chromosomal passenger complex (CPC), which regulates histone modification, chromatid segregation and cytokinesis [Bolton et al, ; Honda et al, ; Vader et al, ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most studied functional AURKA SNP is rs2273535, which was found to be associated with the disease risk in multiple tumor types including colon, breast, lung, and esophagus (57)(58)(59)(60)(61)(62)(63). Another functional AURKA SNP is rs1047972, which was associated with the risk of esophagus cancer as well as with GC progression among the diffuse type patients (16,41). It has been suggested that rs1047972 enhances relative kinase activity of AURKA.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian cells have three types of Aurora kinases, AURKA, AURKB, and AURKC which have specific subcellular localizations and functions during cell cycle . Aurora kinase A (AURKA) is a well‐known oncogene and serin/threonin kinase , which is localized at the centrosome from the moment of centrosome duplication to mitotic completion, and separates to the spindle poles and spindle microtubules during mitotic division . Therefore, AURKA plays pivotal role in centrosome function and spindle assembly .…”
Section: Introductionmentioning
confidence: 99%